Aktivitas fisik moderat meningkatkan rasio jumlah otot polos dan kolagen pada penis tikus tua (Rattus norvegicus) - Raoulian Irfon; I Nyoman Mangku Karmaya; Yuliana . (Bali Anatomy Journal, 2018)
Aging process is related with the increase of free radicals numbers that will lead to destruction of body structures including penis by the degradation of smooth muscle and the increasing of collagen numbers. Moderate physical activity is prospected to have an antioxidant effect that will maintain the penis structure. Aim: The aim of this study it to determine that the physical activity can increase the ratio of smooth muscle and collagen in penis of aged mice. Methods: This study was experimental posttest only control group design. Fourteen 18-month old mice were divided into two group, control and test group. Swimming 30 minutes/day for 8 weeks was conducted on the test group. After 8 weeks experiment, Corpus cavernosum were then collected from the mice and stained with Sirius red staining. The penis preparation were examined under the microscope and analyzed with photoshop cs 6 to get the pixel amounts of smooth muscle and collagen. Results: The result shows the mean of smooth muscle and collagen ratio for control group is 0.156 ± 0.021 and 0.312 ± 0.005 for the test group. This result shows that there is a difference between the smooth muscle and collagen ratio between the control and test group (p < 0.05). The smooth muscle and collagen ratio is higher in the test group than the control group. Conclusion: The physical activity increases the smooth muscle and collagen ratio in penis of aged mice (Rattus norvegicus).